Bibliometric and visualized analysis of myopic corneal refractive surgery research: from 1979 to 2022 - Yang, Fang; Dong, Yi; Bai, Chen; Alzogool, Mohammad; Wang, Yan (Frontiers in Medicine, 2023)
Background: Corneal refractive surgery is one of the most common ophthalmic procedures for correcting ametropia. This study aimed to perform a bibliometric analysis of research in the field of corneal refractive surgery over the past 40 years to characterize the current international status of corneal refractive surgery and identify its most influential factors, in addition to exploring research hotspots. Methods: Based on the Web of Science Core Collection (WoSCC), bibliometric analysis was conducted to investigate publication trends in research related to corneal refractive surgery. Knowledge maps were constructed using VOSviewer v.1.6.10 to visualize the publications, distribution of countries, international collaborations, author productivity, source journals, cited references, keywords, and research hotspots in this field. Results: A total of 4,680 publications on corneal refractive surgery published between 1979 and 2022 were retrieved. The United States has published the most papers. Emory University contributed the most to the citations. The Journal of Cataract and Refractive Surgery is the most prolific in this field, and the top ten cited references mainly focused on outcomes and wound healing in refractive surgery. Previous research emphasized "radial keratotomy (RK)" and excimer laser-associated operation methods. The keywords containing femtosecond (FS) laser associated with "small incision lenticule extraction (SMILE)" and its "safety" had higher burst strength, indicating a shift of operation methods and coinciding with the global trends in refractive surgery. The document citation network was clustered into five groups: 1. outcomes of refractive surgery: 2. preoperative examinations for refractive surgery were as follows: 3. complications of corneal refractive surgery; 4. corneal wound healing and cytobiology research related to photorefractive laser keratotomy; 5. biomechanics of corneal refractive surgery. Conclusion: The bibliometric analysis in this study may provide scholars with valuable information and help them better understand the global trends in corneal refractive surgery research frontiers. Two stages of rapid development occurred around 1991 and 2013, shortly after the innovation of PRK and SMILE surgical techniques. The most cited articles mainly focused on corneal wound healing, clinical outcomes, ocular aberration, corneal ectasia, and corneal topography, representing the safety of the new technique.